Determinants of islamic banks profitability in Malaysia / Ummi Farha Nadhira Mohamed Farouk - Mohamed Farouk, Ummi Farha Nadhira (2017)
Islamic banking are one of the source of contribution to the economy in Malaysia since the establishment of the Malaysia's first Islamic bank namely Bank Islam Malaysia Berhad (BIMB) in 1983. Since Malaysia is one of the countries that have implemented the concept of Islamic finance in its banking industry, the Islamic banking system is widely accepted by Muslims as well as non-Muslim and shown a better youth in this country. Malaysia has been successful implement a dual banking system where the full-fledge Islamic banking system are operated on a parallel basis with the conventional banking system. The positive development of Islamic banking system are contribute to this study. This study was conducted to examine the determinants of profitability for Islamic Banking institutions in Malaysia which are listed on the Bursa Malaysia. The gathered data were from 8 Islamic banks operating in Malaysia with the period of study 6 years started from 2010 to 2015. The Islamic Banking Institutions that are been selected are consists of 8 institutions which is Bank Islam Malaysia Berhad (BIMB), Bank Muamalat Malaysia Berhad (BMMB), Affin Islamic bank, Alliance Islamic bank, CIMB Islamic, Maybank Islamic, Public Bank Malaysia Islamic, and RHB Islamic bank. All those 8 Islamic Banking Institutions are included as a sample because it is among the popular Islamic Banking in Malaysia and because of the availability of data. The bank profitability are measured by Return on Asset (ROA) and the bank specific determinants are consists of Bank size, capital adequacy, liquidity, credit risk, and expenses management. This study are analyse. using Panel data.